Stability of Borderline Personality Disorder Features in Girls - Stepp, Stephanie D. (2010)
Little empirical evidence exists regarding developmental antecedents of borderline personality disorder (BPD) features in children and adolescents. As a first step in addressing this gap in our knowledge, this study examined the factor structure and stability of putative underlying BPD features, specifically impulsivity, negative affectivity and interpersonal aggression, in 6–12 year-old girls. We report on results from exploratory and confirmatory factor analyses of underlying BPD dimensions as rated by parents and teachers over six successive data waves in a large, community sample of girls (N=2,451). Six factors were derived from parent ratings (i.e., Cognitive Dyscontrol, (Lack of) Self-Control, Hostility, Depression/Anxiety, Hyperactivity, and Relational Aggression) and five factors were derived from teacher reports (i.e., Cognitive Dyscontrol, Hyperactivity, (Lack of) Self-Control, Relational Aggression, and Depression). The item composition of similar parent and teacher factors was highly consistent. The year-to-year stability from ages 6 to 12 was high for parent factor scores (r ranging from .71–.85) and moderately high for teacher factor scores (r ranging from .49–.77). These findings suggest that underlying dimensions of BPD features can be reliably measured and are stable in 6–12 year-old girls.